MOLECULAR INVESTIGATION OF CLOSTRIDIUM SEPTICUM IN THE GASTROINTESTINAL TRACTS OF CATTLE IN SOUTHWEST NIGERIA - Tenny, O. G. E.; Oluwaseyi, G. O.; Esther, I. E.; Bisola, V. O.; Folasade, T. O. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study was conducted to determine the prevalence of Clostridial species and toxigenic Clostridium septicum in beef cattle present in abattoirs of southwestern Nigeria. Faecal samples were collected from 108 cattle in three abattoirs from Lagos and Oyo states, Nigeria. Isolation and tentative identification of anaerobic bacteria was performed according to standardized procedure, and served as inclusion criteria for further analysis. DNA was extracted from selected samples and polymerase chain reaction (PCR) performed using Clostridia 16SrRNA, triosephosphate isomerase (tpi), and Clostridium septicum alpha toxin (csa) primers. The PCR products were purified with exo sap and subjected to Sanger sequencing. A total of 64 samples were selected for analysis based on the isolation of obligately anaerobic Gram positive, catalase and oxidase negative, motile bacteria. A total of 21 (32.8%) Clostridia species were identified by PCR amplification of the 16SrRNA and tpi gene regions, and 19 toxigenic C. septicum identified by csa amplification. Uncultured Clostridia, and Clostridium tetani were identified by sequencing and a phylogenetic tree constructed with the nucleotide sequences. The presence of C. Septicum and in the largest abattoir in West Africa poses a significant health risk to the inhabitants of the state.